2023
DOI: 10.1001/jama.2023.20134
|View full text |Cite
|
Sign up to set email alerts
|

Landiolol and Organ Failure in Patients With Septic Shock

Tony Whitehouse,
Anower Hossain,
Gavin D. Perkins
et al.

Abstract: ImportancePatients with septic shock undergo adrenergic stress, which affects cardiac, immune, inflammatory, and metabolic pathways. β-Blockade may attenuate the adverse effects of catecholamine exposure and has been associated with reduced mortality.ObjectivesTo assess the efficacy and safety of landiolol in patients with tachycardia and established septic shock requiring prolonged (>24 hours) vasopressor support.Design, Setting, and ParticipantsAn open-label, multicenter, randomized trial involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 36 publications
0
20
1
Order By: Relevance
“…To the Editor The use of β-blockers during septic shock aims to counter adrenergic stress and may be justified by the early reduction in deleterious effects resulting from sympathetic overactivation. Contrary to a previous study, the authors of the Study Into the Reversal of Septic Shock With Landiolol (STRESS-L) conclude that an infusion of landiolol did not reduce organ failure, and thus, the results of the study do not support its use among patients treated with norepinephrine for established septic shock.…”
contrasting
confidence: 85%
“…To the Editor The use of β-blockers during septic shock aims to counter adrenergic stress and may be justified by the early reduction in deleterious effects resulting from sympathetic overactivation. Contrary to a previous study, the authors of the Study Into the Reversal of Septic Shock With Landiolol (STRESS-L) conclude that an infusion of landiolol did not reduce organ failure, and thus, the results of the study do not support its use among patients treated with norepinephrine for established septic shock.…”
contrasting
confidence: 85%
“…A previous study found that short-acting beta-blockers such as esmolol and landiolol are able to efficiently control tachycardia in patients with sepsis without any relative decrease in the mean arterial pressure, and improve patient survival ( 40 ). However, recently published STRESS-L RCT ( 41 ) has revealed that in patients with septic shock and tachycardia that were managed by norepinephrine for >24 h, the use of beta-blocker landiolol did not affect SOFA scores or mortality rates. The trial had to be stopped prematurely due to the possible adverse effects of beta-blockers.…”
Section: Discussionmentioning
confidence: 98%
“…Although β-blockers are effective in reducing HR, they also have a negative inotropic effect and thus may be potentially harmful in MODS patients with myocardial dysfunction [3,5]. These concerns are even supported by the premature interruption of the recent STRESS-L randomized trial using landiolol, a highly β1-selective blocker, for an increase in mortality and severity of organ dysfunction at 28 days associated with the use of this drug [47]. Similar issues emerge from the multi-center randomized J-Land 3S trial [48], where adverse events occurred in 64% of patients in the landiolol group, with serious adverse events, including events leading to death, in 12% of patients.…”
Section: Hemodynamic Changes In Sepsismentioning
confidence: 99%